PROSES KREATIVITAS SANGGAR GALATIAK MINANG KOTA PADANG - Reren Rachma Dwiyanti; Hendri Yusuf (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the creative process that occurs at the Galatiak Minang Dance Studio in Padang City. This type of research is qualitative research with a descriptive method. The research instrument is the researcher themselves, assisted by observation, interview, and documentation guidelines. Data collection techniques are carried out by observing practice activities, interviewing the studio leader (Rika Astika) and instructors, and documenting studio activities. Data analysis uses the 4P creativity theory (Person, Press, Process, Product). The results of the study indicate that the creative process at Galatiak Minang Studio is formed through four main aspects: (1) Personal (Person): The figure of the studio leader who has an independent character, is disciplined, and brave in experimenting (trial and error) despite not having a formal higher education in the arts; (2) Supporter (Press): There is strong internal support from the husband and coaches, as well as external support from the enthusiasm of parents who are actively involved in event preparations; (3) Process (Process): Carried out through a disciplined routine training schedule, periodic evaluations through promotion exams, and the courage to independently organize annual competitions; (4) Product (Product): Produces various new dance creations based on tradition such as the Cewang Batok Harvest Dance, Silincah Tabang, and Galatiak Piriang, as well as producing accomplished dancers at both local and regional levels.